Pengaruh Latihan Reaksi terhadap Performance Goalkeeper - Hidayat, Ryan Ahmad; Permadi, Asep Angga; Hermawan, Irwan (Universitas Hamzanwadi, 2022)
Goalkeepers have a very big role in the game of football. Attack and defense in football game starts from the goalkeeper. The Goalkeeper just has good concentration and speed to play football. According to observations made by researchers, the obstacles that exist in football goalkeepers are the ability to reaction speed and performance during match due to the lack of variation training method. Therefore, with the goalkeeping reaction training, it is expected to be able to train skills, especially reaction speed and performance when competing well which can support the quality of soccer goalkeepers. The purpose of this study was to determine whether there was an effect to reaction training on reaction speed and goalkeeper performance during matches. The research is an experimental study using the a pretest-posttest design. The population in this study were all 10 goalkeepers at the SSB Putra Bungbulang. The technique used to sample is a saturated sampling technique. Data analysis on the study are normality test, homogeneity test, and hypothetical test. Based on the result of the data analysis carried out, it was stated that there was a significant increase in reaction training on the performance of the goalkeeper at SSB Putra Bungbulang as evidenced by a significance value of Significant (2-tailed) 0,000<0,05.